Both diet and Helicobacter pylori infection contribute to atherosclerosis in pre- and postmenopausal cynomolgus monkeys - Testerman, Traci L. (PLoS One, 2019)
A number of viruses and bacterial species have been implicated as contributors to atherosclerosis, potentially providing novel pathways for prevention. Epidemiological studies examining the association between Helicobacter pylori and cardiovascular disease have yielded variable results and no studies have been conducted in nonhuman primates. In this investigation, we examined the relationship between H. pylori infection and atherosclerosis development in socially housed, pre- and postmenopausal cynomolgus macaques consuming human-like diets. Ninety-four premenopausal cynomolgus monkeys (Macaca fascicularis) were fed for 36 months an atherogenic diet deriving its protein from either casein lactalbumin(CL) or high isoflavone soy (SOY). Animals were then ovariectomized and fed either the same or the alternate diet for an additional 36 months. Iliac artery biopsies were obtained at the time of ovariectomy and iliac and coronary artery sections were examined at the end of the study. Evidence of H. pylori infection was found in 64% of the monkeys and 46% of animals had live H. pylori within coronary atheromas as determined by mRNA-specific in situ hybridization. There was a significant linear relationship between the densities of gastric and atheroma organisms. Helicobactor pylori infection correlated with increased intimal plaque area and thickness at both the premenopausal and postmenopausal time points and regardless of diet (p< 0.01), although animals consuming the SOY diet throughout had the least amount of atherosclerosis. Additionally, plasma lipid profiles, intimal collagen accumulation, ICAM-1, and plaque macrophage densities were adversely affected by H. pylori infection among animals consuming the CL diet, while the SOY diet had the opposite effect. Plaque measurements were more highly associated with the densities of cagA-positive H. pylori within coronary atheromas than with the densities of gastric organisms, whereas plasma lipid changes were associated with H. pylori infection, but not cagA status. This study provides strong evidence that live H. pylori infects atheromas, exacerbates atherosclerotic plaque development, and alters plasma lipid profiles independently of diet or hormonal status. Finally, socially subordinate animals relative to their dominant counterparts had a greater prevalence of H. pylori, suggesting a stress effect. The results indicate that early H. pylori eradication could prevent or delay development of cardiovascular disease.